There are many ways to do good (Analytical Study of the Bayān Kathrot Ṭuruq Al-Khair Chapter in the Book of Riyadh Al-Shalihin) - Achmad Nur Mawalid (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
This study discusses the many pathways to doing good in the context of Islamic teachings, focusing on two important hadiths found in the book Riyadh Al-Shalihin by Imam an-Nawawi. The first hadith, from Abu Dharr Radhiallahu ‘Anhu, emphasizes the prohibition against belittling any good deed, no matter how small, and illustrates that a simple act like greeting someone with a cheerful face can have a significant positive impact on others. The second hadith, from Jabir Radhiallahu ‘Anhu, states that every good deed is considered a charity (sadaqah), reinforcing that all actions performed with good intentions bring one closer to Allah SWT. The analysis of these two hadiths demonstrates that there is no excuse for a Muslim to shy away from doing good, as every positive action, no matter how small, holds great value and reward. Thus, this study provides a deeper understanding of the important role of goodness in daily life and its relevance amidst current social challenges.